Applying Audio lingual Method in English lessons - Dildora Shamsiddinovna, Ibragimova; Nasiba Bakhtiyarovna, Zayniyeva (International Journal of Psychosocial Rehabilitation, 2020)
The beneficial use of technique in teaching assists the students to enjoy the learning process. The effective technique of teaching in the learning process can be seen in the performance or the goal. The goal of learning a foreign language is to master the target language. In a general way, the foreign language, like English, is studied by the learner in the secondary school. The technique of teaching has been made to reduce the failures of learning a foreign language. Speaking and listening are important skills in learning English. Due to the significance of speaking and listening itself, there are some functions of speaking and listening for the users and respondents. The functions of those can be seen clearly in the application of speaking in daily life, such as to communication, expressing the idea orally, giving command to other persons, etc. In addition, the method of learning speaking and listening must be taken in the learning process to achieve the goal of learning foreign language. Based on the previous explanation, it is intriguing to find out the method that is appropriated with the technique of teaching speaking and listening. However, there are many methods of teaching speaking, such as The Direct Method, the audio-linguistic Method, The Grammar Translation Method, etc. Therefore, this paper will focus on the application of the audio-linguistic method in an English-speaking class.